The Commercial Street as "Frozen" Festival: A Study in Chinese Mercantile Traditions. Issue 3 (2nd September 2018) - Gao, Yun; Temple, Nicholas; Li, Yan
ABSTRACT: Amidst the skyscrapers of many contemporary Chinese cities, commercial streets have emerged in traditional Chinese styles that serve as places to host festive celebrations and to satisfy everyday leisure and commercial needs. Buildings along these streets operate at one level as ritual "encasements" that frame festival processions, and thereby "speak" of ceremonial meanings. These framing devices constitute material remnants of past festival events, periodically reactivated as public spectacles or during momentary episodes of individual or collective recollection. This study explores themes relating to these intersections between building and festive occasion through an examination of two traditionally designed commercial streets in China. It argues that architecture in these two cases presents in different ways a "foregrounding" of festivals, in which participants are reminded of previous events. Architectural elements and their details serve as substitutes for words, recapitulating the verbal and gestural meanings of festivals through design language.